2003
DOI: 10.1046/j.1461-0248.2003.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infections and insect–pathogen interactions

Abstract: Most studies of insect–pathogen interactions consider the direct interaction between one disease agent and one species of host. However, given that hosts are subject to challenge from many pathogen/parasite species, mixed infections are probably common. In this study, using the desert locust and two species of fungal entomopathogen, we show how mixed infection with a largely avirulent pathogen can alter the virulence and reproduction of a second, highly virulent pathogen. We find that two strains of the avirul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 49 publications
5
78
1
Order By: Relevance
“…Few studies have addressed interactions between multiple insect pathogens within one host, but evidence to date indicates that pathogens may act either in synergy or interference when they infect the same host individual (Malakar et al 1999b, Ishii et al 2002, Thomas et al 2003, Hughes and Boomsma 2004. Virtually all studies of co-infection of insect hosts have been conducted in laboratory settings and have provided some evidence that infection by one pathogen may alter the host's physiology and make it more or less suitable for a second pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have addressed interactions between multiple insect pathogens within one host, but evidence to date indicates that pathogens may act either in synergy or interference when they infect the same host individual (Malakar et al 1999b, Ishii et al 2002, Thomas et al 2003, Hughes and Boomsma 2004. Virtually all studies of co-infection of insect hosts have been conducted in laboratory settings and have provided some evidence that infection by one pathogen may alter the host's physiology and make it more or less suitable for a second pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the host's environment is another factor that is known to aVect the eVect of single infections on host phenotype (Bedhomme et al 2004;Fellous and Salvaudon 2009;Vale et al 2008). But the inXuence of environmental quality in cases of co-infections is less well known (Thomas et al 2003). In order to examine this question, we also varied the quantity of food given to the host larvae.…”
Section: Introductionmentioning
confidence: 99%
“…In mixed infections, complex interactions between pathogens and host may arise, so the burden of one or both of the infectious agents may be increased and the other suppressed [21,22]. The nature of any specific infection in a host concurrently infected with a particular pathogen may be very different from an infection caused by the same agent in a host co-infected with another pathogen or in a host that is otherwise uninfected [21,23].…”
Section: Interacting Infectious Agentsmentioning
confidence: 99%
“…One area where mixed infection has attracted considerable attention in recent years is in the study of evolution of virulence [24][25][26][27]. Thomas et al [22] demonstrated that avirulent pathogens, which have been given little attention and may go largely undetected in the field, can play a significant role in mediating the outcome of coupled host-pathogen interaction when these agents occur in mixed infections. Models and data indicated that mixed infection can lead to the evolution of either increased or decreased virulence.…”
Section: Interacting Infectious Agentsmentioning
confidence: 99%